Administration of Boiled Moringa Leaf Extract to Lower High Blood Pressure in Hypertensive Patients - Marini Marini; Ika Permanasari; Destria Efliani; Suci Amin (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a significant health issue as it serves as a major risk factor for various diseases, including heart disease, kidney failure, diabetes mellitus, and stroke. One pharmacological method that can help lower blood pressure is consuming boiled moringa leaf (Moringa oleifera) extract. This study aims to analyze the effects of consuming boiled moringa leaf extract on reducing blood pressure in individuals with hypertension in Sebauk Village, within the working area of Meskom Public Health Center, Bengkalis District. This study employed a case study method with a descriptive design. The research findings indicate that before consuming boiled moringa leaf extract, the systolic blood pressure of the respondents ranged from 145 mmHg to 165 mmHg, with an average of 152.81 mmHg. Meanwhile, the diastolic blood pressure ranged from 90 mmHg to 120 mmHg, with an average of 96.19 mmHg. After the administration of boiled moringa leaf extract, the systolic blood pressure of the respondents decreased, ranging from 130 mmHg to 160 mmHg, with an average of 138.44 mmHg. Additionally, the diastolic blood pressure dropped to a range of 80 mmHg to 100 mmHg, with an average of 85.31 mmHg. Based on these findings, it is recommended that Meskom Public Health Center educate the community about the risks of hypertension and its prevention and management, including consuming boiled moringa leaf extract as a natural alternative to help lower blood pressure.